2016
DOI: 10.4103/0972-0707.186457
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of randomized controlled trials on sterilization methods of extracted human teeth

Abstract: Aim of this Study:The aim was to evaluate the efficiency of different sterilization methods on extracted human teeth (EHT) by a systematic review of in vitro randomized controlled trials.Methodology:An extensive electronic database literature search concerning the sterilization of EHT was conducted. The search terms used were “human teeth, sterilization, disinfection, randomized controlled trials, and infection control.” Randomized controlled trials which aim at comparing the efficiency of different methods of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…They also estimate that there is a 2% risk associated with Hepatitis C Virus (HCV) and 6-30 % (if the affected person is not vaccinated) from patients infected with Hepatitis B Virus (HBV). 25 Considering that many students have low HBV and Hepatitis A Virus (HAV) antibody values and that there is a risk of both direct transmission and cross-infection in their preclinical education 16,17 , the rates of not reporting injuries are worrying. In addition, almost all of the students, who had not yet been injured in preclinical courses, stated that they would report their injuries after possible accidents which they may experience in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also estimate that there is a 2% risk associated with Hepatitis C Virus (HCV) and 6-30 % (if the affected person is not vaccinated) from patients infected with Hepatitis B Virus (HBV). 25 Considering that many students have low HBV and Hepatitis A Virus (HAV) antibody values and that there is a risk of both direct transmission and cross-infection in their preclinical education 16,17 , the rates of not reporting injuries are worrying. In addition, almost all of the students, who had not yet been injured in preclinical courses, stated that they would report their injuries after possible accidents which they may experience in the future.…”
Section: Discussionmentioning
confidence: 99%
“…1,14,15 Students who receive preclinical education should take the same precaution in preclinical injuries, even if they are not in direct contact with infectious substances such as the patient's blood and saliva. 16 The Occupational Safety and Health Administration's (OSHA) Bloodborne Pathogens Standard recognizes human teeth as a potential source of blood-borne pathogens. 17 In a study evaluating sterilization methods applied to human extracted teeth, it was stated that commonly used sodium hypochlorite sodium hypochlorite solutions (5.25 %) were insufficient and unreliable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review by Western and Dicksit concluded that autoclaving, and formalin could be efficiently used for sterilisation of extracted teeth. Their use was discouraged, as autoclaving disrupts organic matrix of the tooth and formalin possess a major health hazard as a potential carcinogen [29]. The authors of the current study aimed for intermediate disinfection time, as performed by a previously [19].…”
Section: Discussionmentioning
confidence: 99%
“…Thymol was also used to disinfect primary teeth in previous researches studying laser assisted remineralisation [22]. However, the authors of this study preferred the use of sodium hypochlorite due to its superior efficacy [29]. Teeth were air dried for only 3 sec before DD measurements as prolonged drying increases the fluorescence readings [21].…”
Section: Discussionmentioning
confidence: 99%